Evaluation of pregnancy rates following timed AI in beef heifers after synchronization of follicular waves using a 14-d controlled internal drug release insert, and the lifetime productivity of beef heifers conceiving to, or sired by, AI - French, Jesse, author; Peel, Kraig, advisor; Holt, Timothy, committee member; Ahola, Jason, committee member; Whittier, Jack, committee member (Colorado State University. Libraries, 2012)
Three studies were conducted to evaluate the efficacy of a timed AI (TAI) estrous synchronization protocol that used a 14-d controlled internal drug release (CIDR) insert and a GnRH injection on d 9 to force ovulation of potentially persistent follicles and induce a second wave of follicle growth. In the first study 710 yearling heifers across 4 locations were assigned to 1 of 3 treatments: 1) 14-d GnRH-9 heifers (n = 242) received CIDR (1.38 g progesterone) and 100 μg GnRH on d 0, 100 μg GnRH on d 9, and 50 mg PGF2α on d 14 concurrent with CIDR removal, 2) 14-d 6 h PG heifers (n = 233) were identical to 14-d GnRH-9 except that on d 14, 2 25 mg injections of PGF2α were given 6 h apart, and 3) 5-d CO-Synch + CIDR heifers (n = 235) received 100 μg GnRH and CIDR on d 9 and a single 25 mg PGF2α at CIDR removal. All 3 treatments received 100 μg GnRH with TAI at 72 ± 2 h after CIDR removal. The 14-d GnRH-9 TAI pregnancy rate (54.5%) did not differ (P = 0.57) from the 14-d 6h PG TAI pregnancy rate (53.6%). The TAI pregnancy rate of 14-d protocols combined was 54.1%, and was not different (P = 0.20) from the 5-d CO-Synch + CIDR TAI pregnancy rate of 46.4%. The following year 319 yearling heifers across 4 locations were assigned to 1 of 3 treatments: 1) 14-d GnRH-9 (n = 107; as described earlier), 2) 14-d PG (n = 107) was identical to 14-d GnRH-9 except instead of receiving GnRH on d 0 they received 25 mg of PGF2α and, 3) 5-d CO-Synch + CIDR (n = 104; as described earlier). All treatments received 100 μg GnRH at TAI 72 ± 2 h after CIDR removal. Heifers' ovaries (n = 120) were ultrasounded at 2 locations on d 0, 9, 14, and 17 of the estrous synchronization protocol to determine ovarian structures and response. The 14-d GnRH-9 TAI pregnancy rate (52.3%) was not different (P = 0.82) than 14-d PG (47.6%), nor was the TAI pregnancy rate of both 14-d treatments combined (50.0%) different (P = 0.66) from 5-d CO-Synch + CIDR (47.1%). Based on ultrasonography, the 14-d GnRH-9 treatment induced a second wave of follicular growth in 25.9% of heifers while 14-d PG heifers had larger (P = 0.01) follicle size on d 9 but did not reduce (P > 0.10) corpora lutea at TAI compared to 14-d GnRH-9 or 5-d CO-Synch + CIDR. That same year 453 heifers at another location were assigned to 1 of 3 treatments: 1) 14-d GnRH-9 (n = 150; as described earlier), 2) 14-d GnRH-7 (n = 150) received 100 μg GnRH and CIDR on d 0, 100 μg GnRH on d 7, 25 mg PGF2α on d 14 at CIDR removal, and 100 μg GnRH at TAI 63 ± 3 h after CIDR removal, and 3) 7-d CO-Synch + CIDR received 100 μg GnRH and CIDR on d 7, 25 mg PGF2α at CIDR removal, and 100 μg GnRH at TAI 63 ± 3 h after CIDR removal. Pregnancy rate to TAI of 14-d GnRH-9 (51.3%) was not different (P = 0.75) than 14-d GnRH-7 treatment (48.0%), nor was the TAI pregnancy rate of both 14-d treatments (49.6%) different (P = 0.83) from 7-d CO-Synch + CIDR (48.6%). These data indicate that the 14-d CIDR estrous synchronization protocol with d 9 GnRH produces comparable pregnancy rates to TAI compared to the industry utilized 5-d and 7-d CO-Synch + CIDR estrous synchronization protocols. However, the additional labor and pharmaceutical cost of handling heifers on d 9 raises the question whether it's a viable TAI estrous synchronization alternative. The final experiment evaluated the lifetime productivity of heifers conceiving to AI or natural service (NS), and heifers sired by AI vs. NS. Calving and breeding records (n = 6,693) at one location for 1,173 Angus females and were obtained from 1991 to 2010. Lifetime weight weaned, calves weaned, and revenue produced was determined and analyzed. Heifers that conceived to AI had greater (P < 0.0001) lifetime weight weaned, lifetime calves weaned, lifetime revenue, and greater (P < 0.05) average annual weaning weight than heifers that conceived to NS. There was no difference (P > 0.10) in average annual weaning weight, lifetime weight weaned, lifetime calves weaned, or lifetime revenue produced between heifers sired by AI or NS. Estrous synchronization and AI can be a valuable tool to produce replacement heifers that conceive earlier, and in doing so increase their lifetime productivity.
Keywords: artificial insemination; heifers; follicular waves; estrous synchronization